The long-term effects of the operations of the Agricultural Bank in supporting per capita GDP in syria during the period 2000-2020 - زريق مروج; ايمن العشعوش; محمد محمود (Latakia University Journal - Economic and Legal Sciences Series, 2023)
where agricultural lending is one of the most important factors driving production forward, and agricultural loans play a major role in the Syrian economy in light of the fact that agriculture is one of the important economic activities. In terms of its contribution to the gross domestic product, Therefore, the research aims to the role played by the Agricultural Bank in its operations of lending and accepting deposits in order to secure the funding necessary to implement the agricultural plan that contributes to supporting agricultural and rural development, which in turn contributes to supporting agricultural production and thus its reflection in supporting development economic and social, and in order to reach results and proposals that contribute to improving the important role played by the Agricultural Cooperative Bank represented by all its branches, and the research reached the following results: The existence of a long-term impact of the cash credit of the Agricultural Bank on economic development, and therefore improving the management of this credit in the long term is positively reflected in the economic development in Syria. The existence of a direct long-term effect of the Agricultural Bank deposits on the per capita GDP, as every increase in the amount of deposits by one unit is accompanied by an increase of 2,183 units in the per capita GDP, as this effect is due to the fact that these deposits are used by banks in agricultural investments. We conclude that there is an inverse long-run effect of the Agricultural Bank loans on per capita GDP, since every increase in the amount of loans by one unit is accompanied by a decrease of 0.684 units in per capita GDP. Because these amounts increase the supply of credit and pressure on agricultural inputs that the market suffers from scarcity after 2011, and these loans may be used in another field, which is negatively reflected in per capita GDP.